Performance Evaluation and Management Method of Music Tutoring Schools Based on Analytic Hierarchy Process - Li Wang (Discrete Dynamics in Nature and Society)
On the basis of summarizing the relevant theories of performance management at home and abroad, the important role, significance, and development trend of performance management in music tutoring schools are analyzed. Starting from the actual management of music tutoring schools, taking a music tutoring school as an example, this article comprehensively analyzes the current situation of the school’s performance assessment. Considering that the constructed index system is a multilevel comprehensive index system, the analytic hierarchy process is used to give weight to the index. The calculation method and calculation steps are described in detail, and the weight of each index is obtained. Through the design and implementation of the school’s performance management system, solid theoretical and institutional support will be provided for the school to achieve sound development in the future. It is expected that the design of this performance can provide reference for such private schools in the country and promote the healthy and sustainable development of private training institutions in China. Let more schools and learners share the nectar and dividends brought by the system reform.